2022
DOI: 10.1121/10.0009237
|View full text |Cite
|
Sign up to set email alerts
|

Offshore wind energy development: Research priorities for sound and vibration effects on fishes and aquatic invertebrates

Abstract: There are substantial knowledge gaps regarding both the bioacoustics and the responses of animals to sounds associated with pre-construction, construction, and operations of offshore wind (OSW) energy development. A workgroup of the 2020 State of the Science Workshop on Wildlife and Offshore Wind Energy identified studies for the next five years to help stakeholders better understand potential cumulative biological impacts of sound and vibration to fishes and aquatic invertebrates as the OSW industry develops.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Several studies have described the various impacts of PD on many marine taxa, ranging from temporary changes in behavior to mortality 5 7 . However, the impacts of substrate-borne vibrations from hammering piles into the seabed remain poorly understood 8 10 . This benthic component travels farther and faster than the water-borne signal generating concerns for benthic taxa 8 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have described the various impacts of PD on many marine taxa, ranging from temporary changes in behavior to mortality 5 7 . However, the impacts of substrate-borne vibrations from hammering piles into the seabed remain poorly understood 8 10 . This benthic component travels farther and faster than the water-borne signal generating concerns for benthic taxa 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed bivalves respond to low frequencies (i.e., < 1 kHz) by closing their valves 12 . However, the translation of these laboratory experimental results into the field are not yet clear, especially when considering the differing intensities as well as the spatial and temporal scales of potential impacts by anthropogenic activities 10 . Currently, only one field study has described noise impacts on adult scallops.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations